PENGARUH GAYA HIDUP KONSUMTIF TERHADAP MINAT MENABUNG PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS SRIWIJAYA - Vinna Ameylinda; Dwi Hasmidyani (Al-Mubin, 2026)
The consumerist lifestyle that students tend to follow can influence their interest in saving. This study aims to determine whether there is an influence between a consumerist lifestyle and the interest in saving among Economics Education students at the Faculty of Teacher Training and Education, Sriwijaya University. The research method used was quantitative with a causal associative approach. Data collection techniques used were questionnaires and interviews. The study sample consisted of 156 students using random sampling. Data analysis techniques used were prerequisite test analysis with normality and linearity tests, and hypothesis testing with simple linear regression. The results of the normality test analysis indicate that the consumerist lifestyle and interest in saving variables are normally distributed. The results of the linearity test indicate that the data have a linear pattern. The results of the hypothesis test analysis prove that there is an influence between a consumerist lifestyle and interest in saving among Economics Education students at the Faculty of Teacher Training and Education, Sriwijaya University, with an effect of 2.49%. This study is expected to encourage students to improve their economic literacy and financial awareness to avoid a consumerist lifestyle.